Perilaku Bullying Sekolah : Pelaku, Hak Hidup Korban, Dan Kemanusiaan Yang Adil Beradab - Annisa Tri Wahyuni Sulistio; Anisa Pebriani; Reni Kurnia Ramadhan; Siti Rozalina Rohadiyono; Alexandra Florenza Dominggus; Aisyah Purwitasari (Jurnal Relasi Publik, 2024)
Bullying behavior in the school environment is a serious challenge that affects students' welfare and creates a learning environment that is not conducive. This research aims to investigate the dynamics of bullying behavior, focusing on identifying the perpetrator, protecting the victim's right to life, and implementing just, civilized humanity in the educational context. Qualitative research methods were used, by exploring data from document studies, including school policies, bullying incident reports, and student behavior records. The research results show the complexity of the factors driving bullying behavior, involving social inequality, family problems, and a lack of awareness of the consequences of actions. Protection of victims' rights to life is proven to need improvement through evaluating school policies and implementing effective reporting procedures. The implementation of just, civilized human values ​​shows positive steps, however, challenges arise in monitoring and evaluating these programs. The conclusions of this research underscore the urgency of involving teachers, school staff and the entire educational community in efforts to prevent and deal with bullying. With a deep understanding of this problem, it is hoped that a safer, more inclusive and humane school environment can be created